Culture Development Of Baker’s Yeast In Spent Fermentation Broth For Production Of Single Cell Protein - Balasupramaniam, Komathi; Kopli, Bujang (Malaysian applied biology, 2011)
Production of single cell protein in Saccharomyces cerevisiae was studied. The yeast was grown in clear shake-flasks using spent fermentation broth from lab-scale production of ethanol as the sole culture medium. The spent fermentation broth was boiled for 2hrs at 80oC to eliminate all traces of ethanol, producing boiled spent fermentation broth (B-SFB). Growth performance was evaluated based on optical density and protein concentration. Yeast cultured in SFB with 50g/L glucose shows highest growth rate while COD removal in all media was almost same.